Corilagin alleviates atherosclerosis by inhibiting NLRP3 inflammasome activation via the Olfr2 signaling pathway in vitro and in vivo - Mao, Jinqian; Chen, Yunfei; Zong, Qiushuo; Liu, Cuiling; Xie, Jiao; Wang, Yujie; Fisher, David; Hien, Nguyen Thi Thu; Pronyuk, Khrystyna; Musabaev, Erkin; Li, Yiqing; Zhao, Lei; et al. (Frontiers in Immunology, 2024)
Atherosclerosis, a leading cause of global cardiovascular mortality, is characterized by chronic inflammation. Central to this process is the NOD-like receptor pyrin domain containing 3 (NLRP3) inflammasome, which significantly influences atherosclerotic progression. Recent research has identified that the olfactory receptor 2 (Olfr2) in vascular macrophages is instrumental in driving atherosclerosis through NLRP3dependent IL-1 production. Our study employed an atherosclerosis model in ApoE -/- mice, fed a high-fat, high-cholesterol diet, alongside cellular models in Ana-1 cells and mouse bone marrow-derived macrophages, stimulated with lipopolysaccharides and oxidized low-density lipoprotein. We aimed to investigate the effects of Corilagin, noted for its anti-inflammatory attributes, on atherosclerotic development and the Olfr2 signaling pathway. Our findings indicated that Corilagin effectively inhibited NLRP3 inflammasome activation, consequently diminishing inflammation, macrophage polarization, and pyroptosis in the mouse aorta and cellular models via the Olfr2 pathway. This suggests a novel therapeutic mechanism of Corilagin in the treatment of atherosclerosis.